PO.02 Cognitive and neuropsychiatric status in a large cohort of patients with secondary progressive multiple sclerosis. Issue 9 (7th August 2011) - Chataway, J; Awad, M; Meadmore, K; Alsanousi, A; Frost, C; Chandler, K; Merrick, K; Wilkie, D; Nicholas, R; Chan, D
Abstract : Background: The recruitment of secondary progressive multiple sclerosis (SPMS) patients to the MS-STAT trial (a double-blind randomised placebo-controlled trial of high dose simvastatin) provided an opportunity to evaluate the frequency and severity of cognitive and neuropsychiatric symptoms at baseline, in this phase of the disease. The study also explored the interaction between frontal lobe function and neuropsychiatric disorders. Methods: 130 SPMS patients were administered a battery of neuropsychological tests, including the PASAT, the Hamilton Depression Rating Scale and the Neuropsychiatric Inventory. Results: Mean patient age was 50.5 years with mean total MS and SPMS durations of 21.0 years and 7.0 years. Patients demonstrated severe impairment on the PASAT and mild frontal lobe dysfunction. General intelligence, verbal and nonverbal memory, naming and higher visual processing were relatively preserved. 43% of patients had symptoms of depression. There was no association between cognitive and neuropsychiatric test scores or between depression and frontal lobe function. Conclusion: Impaired speed of information processing and frontal lobe function were the most prominent cognitive deficits. A high incidence of depression was also noted. These findings have clear implications for the management of early SPMS.